Аспекти рецепції історії у британському романі 80-90-х років XX століття - Дробіт, І. (Літературознавчі обрії. Праці молодих учених, 2010)
The article covers issues which concern perception of history in the novels of Julian Barnes, Malcolm Bradbury and Graham Swift. Representation of history in fiction is viewed through interconnection of literature and historiography, which can be observed after the so-called «linguistic turn». Main aspects of perception of history in British novels of 1980’s and 1990’s consist in fragmentation and deconstruction of historical past, textualization of history and ironical mode of writing.